Evaluation of long‐term silver supply shortage for c‐Si PV under different technological scenarios. (28th May 2018) - Li, Wenhua; Adachi, Tsuyoshi
Abstract : Abstract: This study focuses on quantifying supply shortage of silver for c‐Si PV over the long term (2015–2050), and measures the effects of technological uncertainties in the industry by scenario. Wherein, Hubbert theory, Weibull distribution, and intensity of demand are used to estimate silver mining supply, recycling supply, and manufacturing demand, respectively. The results show that silver supply shortage for manufacturing demand will occur from 2030. Technology improvements in the PV industry could delay when the shortage begins, but they will not prevent it, while silver supply shortage for c‐Si PV could be eliminated under the total effects scenario. Reducing dependency on silver as a raw material for c‐Si PV industry through technological progress and recycling retired panels is recommended. This study highlights the balance between natural resources and renewable energy sustainability. It benefits the PV industry's long‐term strategizing and helps policy making for long‐term silver resource sustainability. Recommendations for Resource Managers: Technological improvements in the PV industry are critical to relieve silver supply shortage in the long term and ensure sustainable installation of c‐Si PV. Recycling of end‐of‐life c‐Si PV is of great importance to secure silver supply for PV manufacturers in the long term. Improving silver old scrap recycling is necessary for long‐term availability of silver. It is indispensable to balance natural resources and renewable energy sustainability.